Penilaian Sanitasi Dan Analisis Usaha Keripik Pisang Pada Ud Puji Di Desa Parda Suka, Kecamatan Maje, Kabupaten Kaur, Bengkulu - Ujang Karnadi; Lina Widawati; Hesti Nur’aini; Diah Azhari; Hilda Meisya Arif (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This research aims to (1) describe the banana chips production process at UD Puji, (2) analyze and evaluate the sanitation implementation based on Good Manufacturing Practices (GMP) and Sanitation Standard Operating Procedures (SSOP) principles, and (3) analyze business aspects (cost, revenue, and efficiency). A descriptive research method was employed in Parda Suka Village, Kaur Regency, Bengkulu. Data collection involved interviews and direct observation using the SSOP questionnaire. Sanitation analysis utilized Gap Analysis comparing actual conditions with SSOP standards set by FDA (1995) and NSHATE (1999). The banana chips production process at UD Puji includes raw material preparation (kepok banana), peeling, slicing, washing, frying, draining, cooling, seasoning, packaging, and labeling. The sanitation implementation (GMP/SSOP) in aspects of location, building (floor, ceiling, ventilation), and the use of clean water for raw material washing has shown good condition. However, continuous improvement is necessary to achieve full compliance with SSOP standards. The UD Puji banana chip business has a gross income of IDR 4,600,000 with a total cost of IDR 2,355,669 (per week), indicating that the business is efficient.